The Issues of Bank Revenue Analysis - Khubua, Marine (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
A special investigation is required in order to clarify the whole complex of the issues of bank revenue analysis. Banks have a sufficient information base for analysis and in order to carry out the analysis we can use a number of its methods. First of all we must focus on the general methodological development of income analysis and the details of its tasks.